2023
DOI: 10.3390/s23115001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of a Visible Light Communications System Based on Binary Frequency-Shift Keying Modulation: A New Step toward Improved Noise Resilience

Abstract: Visible light communications (VLC) are an emerging technology that is increasingly demonstrating its ability to provide wireless communications in areas where radio frequency (RF) technology might have some limitations. Therefore, VLC systems offer possible answers to various applications in outdoor conditions, such as in the road traffic safety domain, or even inside large buildings, such as in indoor positioning applications for blind people. Nevertheless, several challenges must still be addressed in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Later on, as the design of VLC receivers improved, better tradeoff solutions were integrated. Thus, today's vehicular VLC receivers commonly have ±20 • FoVs [21,[24][25][26], while sometimes reaching ±50 • [25]. Nevertheless, wide FoV VLC receivers are not able to maintain an active link under sunlight conditions, or they may only be able to provide limited communication ranges.…”
Section: Enhancing the Optical Noise Resilience And Compatibility Wit...mentioning
confidence: 99%
See 2 more Smart Citations
“…Later on, as the design of VLC receivers improved, better tradeoff solutions were integrated. Thus, today's vehicular VLC receivers commonly have ±20 • FoVs [21,[24][25][26], while sometimes reaching ±50 • [25]. Nevertheless, wide FoV VLC receivers are not able to maintain an active link under sunlight conditions, or they may only be able to provide limited communication ranges.…”
Section: Enhancing the Optical Noise Resilience And Compatibility Wit...mentioning
confidence: 99%
“…This aspect was pointed out by the authors of [38,39], who intensively investigated the benefits of the direct sequence spread spectrum (DSSS) technique. Their experiments showed that such a system can deal with daylight noise and can enable communication ranges of up to 40 m. The authors of [21] experimentally demonstrated that noise resilience can be improved with the help of binary phase shift keying (BPSK) modulation. This approach enabled the VLC system to better filter the noise, improving the resilience to optical interference by 25% compared to the use of the classical on-off keying (OOK) modulation.…”
Section: Enhancing the Optical Noise Resilience And Compatibility Wit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to emphasize that the system is designed to be compatible with light dimming, making it suitable for energysaving applications while maintaining its blind assistance functions. For situations that imply high optical noise, the concept is also compatible with Binary Frequency-Shift Keying (BFSK) modulation [38], solution that further enhances the system's resilience to noise. In its turn, the VLC receiver represents a vital component of the smart backpack.…”
Section: Visible Light Communications-based Smart Backpack For Visual...mentioning
confidence: 99%
“…Indeed, similar to the Global Positioning System (GPS), which is widely used in outdoor environments, visible light positioning (VLP) can provide the navigation information to find the target indoor destinations. It can therefore be utilized inside large buildings such as for asset tracking in hospitals or universities, for indoor positioning applications for blind people, as well as to provide location-aware services, such as antique information in museums or item prices in shopping malls [11,12].…”
Section: Introductionmentioning
confidence: 99%